2018
DOI: 10.3390/mi9080409
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Laser Manufacturing of Microfluidic Devices from Glass Substrates

Abstract: Conventional manufacturing of microfluidic devices from glass substrates is a complex, multi-step process that involves different fabrication techniques and tools. Hence, it is time-consuming and expensive, in particular for the prototyping of microfluidic devices in low quantities. This article describes a laser-based process that enables the rapid manufacturing of enclosed micro-structures by laser micromachining and microwelding of two 1.1-mm-thick borosilicate glass plates. The fabrication process was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 43 publications
(60 reference statements)
0
41
0
Order By: Relevance
“…The most common techniques used for the generation of flow patterns on glass substrates are reactive ion etching [ 76 , 77 , 78 , 79 , 80 , 81 ] and wet (chemical) etching [ 80 , 81 , 82 , 83 , 84 ]. Other techniques, such as direct laser writing [ 79 , 85 , 86 , 87 , 88 , 89 ], selective laser-induced etching (SLE) [ 90 , 91 , 92 , 93 ], and direct laser writing and laser micro-welding [ 94 , 95 ], are less common, however they are very attractive for the rapid prototyping of microfluidic devices. Moreover, the SLE process enables the generation of complex three-dimensional structures inside glass, as highlighted in Table 1 , and this eliminates additional fabrication steps related to the bonding of two glass plates together.…”
Section: Microfluidic Devices (Physical Micromodels Of Porous Geommentioning
confidence: 99%
See 1 more Smart Citation
“…The most common techniques used for the generation of flow patterns on glass substrates are reactive ion etching [ 76 , 77 , 78 , 79 , 80 , 81 ] and wet (chemical) etching [ 80 , 81 , 82 , 83 , 84 ]. Other techniques, such as direct laser writing [ 79 , 85 , 86 , 87 , 88 , 89 ], selective laser-induced etching (SLE) [ 90 , 91 , 92 , 93 ], and direct laser writing and laser micro-welding [ 94 , 95 ], are less common, however they are very attractive for the rapid prototyping of microfluidic devices. Moreover, the SLE process enables the generation of complex three-dimensional structures inside glass, as highlighted in Table 1 , and this eliminates additional fabrication steps related to the bonding of two glass plates together.…”
Section: Microfluidic Devices (Physical Micromodels Of Porous Geommentioning
confidence: 99%
“…Although the channels manufactured in this way are still at least an order of magnitude larger than the pores and throats in real geomaterials, this process shows potential to become an effective process in the manufacturing of pore network micromodels. Another promising method for the fabrication of enclosed pore network micromodels using glass substrates has been recently developed [ 94 , 95 ]. This method uses an ultrashort pulse laser both for the generation of the network of pores and micro-channels by laser ablation, followed by bonding of glass plates together by laser micro-welding.…”
Section: Summary and Final Remarksmentioning
confidence: 99%
“…By focusing the laser beam inside glass, it is possible to modify locally and permanently some physical properties of the material, e.g., its refractive index. This, in turn, allows the fabrication of two-and three-dimensional microstructures, such as optical waveguides, Bragg gratings, voids, and microchannels [8][9][10][11][12][13], as well as an "adhesive-free" joining of glass to another glass, silicon, or even metals [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This material is commonly used for manufacturing a wide range of products, e.g., optics, microelectronics, and photovoltaics, as well as scientific glassware (beakers, flasks, etc.). Recently, we demonstrated that this glass can also be used for the rapid laser manufacturing of bespoke microfluidic devices [15]. The objective of this article was to investigate the influence of laser parameters and laser beam scanning strategy on the machining throughput and the resulting surface roughness of the laser-machined glass workpiece.…”
Section: Introductionmentioning
confidence: 99%
“…Glass has proved to be a very convenient substrate for microfluidic chips thanks to its insulating properties, mechanical resistance and high solvent compatibility. The prototyping of microfluidic devices in low quantities may be time-consuming and expensive; the article by Wlodarczyk et al describes a laser-based process that enables the fabrication of a fully-functional microfluidic device in less than two hours by using two thin glass plates [7]. The femtosecond laser irradiation followed by chemical etching (FLICE) technique was used by Italia et al to fabricate a buried microfluidic device in a silica substrate; the design was optimized to minimize the diffusive mass transfer between two laminar flows [8].…”
mentioning
confidence: 99%